Pengembangan E-Learning Berbasis Moodle Di SMK AL Washliyah Sumber - Indra Maulana (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2020)
The rapid development of information technology and communication has very large in the formation and progress of the quality of education. Learning methods are also changed in line with technological developments. E-Learning is an innovation in the development of information technology in education. SMK Al Washliyah Sumber plays a role in the development of science, especially in the field of information technology. During this time all learning process at SMK Al Washliyah Sumber is still conventional, in other words, that the learning process between students and teachers can only be done on the condition of meeting between students and teachers in the classroom. The learning process at SMK Al Washliyah Sumber should give the students an expanse of active learning according to the understanding. The learning that can be learned from e-learning is a program designed for the needs of students who can be used in learning activities. The need for communication and information today in school infrastructure is necessary. Increasingly demanding for a system that is fast, easy, inexpensive, effective, and efficient. Therefore, it is necessary to use computer technology to further improve the success of teaching and learning activities by utilizing e-learning Keywords: E-learning, information technology, SMK Al Washliyah